Need of support perceived by patients primarily curatively treated for breast, colorectal, or prostate cancer and close to discharge from hospital—A qualitative study. Issue 9 (19th July 2021) - Hajdarevic, Senada; Fallbjörk, Ulrika; Fransson, Per; Åström, Sture
Abstract: Aim: To describe perceived needs of support among patients close to discharge from the hospital and at the end of primary curative radiotherapy for breast, colorectal or prostate cancer. Background: Few studies have specifically explored patients' early support needs when ending primary curative treatment. Design: Qualitative interview study design. Methods: A purposive sample of 27 participants with breast, colorectal or prostate cancer aged 33–88 years. The interviews were analysed by qualitative content analysis. Reporting followed the COREQ guidelines. Results: Personal support to reach a sense of control and Social support for personal growth were two main themes, highlighting that people required adapted support from health care since needs of support could change over time. This support from health care was also relying on that trust‐based relationships were developed. Through mutuality with others and engagement in meaningful activities people became enabled and felt further supported. Personal support from health care seems specifically important for the patients' feelings of control and could be a facilitator for patients to identify further support for personal growth in how to manage, on the one hand, illness and insecurity, and on the other, their well‐being and everyday life with cancer. Conclusion: To empower patients who are ending primary treatment and being close to discharge from hospital, healthcare professionals should recognise patients' shifting needs and adapt the support. Adapted support is significant for patients' sense of safety. Biomedical information is not sufficient to fully support patients. Relevance to clinical practice: Offering easy access to supportive care when primary treatment is finished could diminish people's stress, insecurity and avoidable use of healthcare services. Even after discharge, nurses preferably should adapt and offer support tailored to patients' needs. Such support may improve patients' sense of control and safety, trust in health care, feelings of community and encourage personal growth.